Fracture predictions based on a coupled chemo-mechanical model with strain gradient plasticity theory for film electrodes of Li-ion batteries - Chen, Y.; Sang, M.; Jiang, W.; Wang, Y.; Zou, Y.; Lu, Chunsheng; Ma, Z. (2021)
High-capacity electrodes in Li-ion batteries inevitably undergo a large volume deformation originating from high diffusion-induced stresses during charging and discharging processes. In this paper, we firstly develop a new elastoplastic model for describing diffusion-induced deformation in the framework of high-density dislocation defects generated due to the migration of Li atoms. Then, we analyze the film size effect, diffusion-induced stress, plastic yielding, and hardening of electrode materials based on the evolutions of Li concentration by a strategy combining the strain gradient plasticity theory and finite element simulations. Finally, according to the traction-separation law, interface damage and debonding are characterized in the active film materials (with a thickness of 150, 200, and 250 nm, respectively) on a rigid substrate.